2021
DOI: 10.3390/biom11020326
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Changes in Human Plasma Lipidome Determined by the Lipidyzer Platform

Abstract: Obesity is an increasing public health concern both in the developed and developing countries. Previous studies have demonstrated that considerable alterations in lipid metabolism and consequently marked changes in lipid profile are associated with the onset and progression of obesity-related complications. To characterize the full spectrum of obesity-induced changes in lipid metabolism, direct infusion tandem mass spectrometry analysis is the most promising approach. To better understand which of the many lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 54 publications
0
23
1
2
Order By: Relevance
“…Studies revealed that LPC was strongly associated with obesity. In particular, obese individuals have low plasma LPC concentrations [53][54][55] , and there is indication that effective and long-term weight loss may restore LPC to normal levels 56 . In case of infancy and childhood overweight/obesity, LPC is strongly related to rapid growth.…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that LPC was strongly associated with obesity. In particular, obese individuals have low plasma LPC concentrations [53][54][55] , and there is indication that effective and long-term weight loss may restore LPC to normal levels 56 . In case of infancy and childhood overweight/obesity, LPC is strongly related to rapid growth.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, plasma lipid profiling of ob/ob mice confirmed circulating lipid biomarkers of obesity. Significantly altered lipid moieties in obese mice plasma recapitulated global obesity-related changes in human plasma lipidome (30, 3335), reinforcing the relevance of using the ob/ob mice as a preclinical model of obesity.…”
Section: Resultsmentioning
confidence: 70%
“…It is no longer restricted by copyright. Anyone can legally obesity-related changes in human plasma lipidome (30,(33)(34)(35), reinforcing the relevance of using the ob/ob mice as a preclinical model of obesity.…”
Section: Lipidomic Analysis Of Obese Mice Plasma Reflects Common Lipid Alterations Associated With Obesitymentioning
confidence: 95%
“…However, several other phospholipid biomarkers provided insight into the health of the mice. Serum LPC concentrations are typically inversely associated with obesity [ 58 ], and specifically, LPC 18 : 2 is inversely associated with childhood obesity, BMI, and metabolic risk factors in humans [ 48 , 58 , 59 ]. Conversely, recent research with murine livers indicates that greater liver LPC concentrations are associated with NAFLD [ 49 ], but inversely associated with NASH [ 6 ].…”
Section: Discussionmentioning
confidence: 99%